Pharmacologic and sensorimotor components of satiation in cigarette smoking - Rose, Jed E; Behm, Frederique M; Westman, Eric C; Bates, James E; Salley, Al (Pharmacology, biochemistry and behavior, 2003)
To examine mechanisms underlying satiation in cigarette smoking, 18 smokers received intravenous (iv) nicotine, alone or in combination with denicotinized cigarette smoke. Nicotine was administered using programmed presentations of either pulsed injections or continuous infusions, with iv saline serving as a control. A high-nicotine cigarette smoke condition (usual brand) was also presented. During each of the six test sessions, subjects were allowed to puff on their usual brands of cigarette ad libitum while the programmed satiation conditions were in force. Administration of iv nicotine caused a small suppression of ad libitum smoking behavior; denicotinized smoke produced a significantly larger reduction, showing that short-term satiation is more dependent on the presentation of smoke than delivery of nicotine per se. However, denicotinized smoke alone did not have as much effect as puffs from the usual brands of cigarettes. The combination of iv nicotine and denicotinized smoke puffs produced equivalent satiation to that of the usual brand. Cigarette craving and negative affect were partially relieved by iv nicotine presentations as well as by denicotinized smoke, and again the combination of iv nicotine and denicotinized smoke approximated the effects of the usual brand. The results of this study underscore the importance of both sensorimotor aspects of smoking and the pharmacologic effects of nicotine in tobacco dependence.